Isolation and food-relevant evaluation of a novel lytic Kayfunavirus phage vB-EcoP-B10 for controlling STEC on food-contact surfaces and in raw beef - Yuxin Mu; Min Li; Xiangqi Bai; Qianhong Li; Xiaodong Xia; Ting Zhou; Chunling Zhang; Ying Yu; Yanna Dai; Jifeng Pu; Hu Pan; Xin Wang (Food Research International, 2026)

Carbonate rock-SRB system driven by high-concentration organic wastewater: Performance and mechanism for synergistic AMD remediation - Yisheng Mu; Jiajun Zou; Ruixue Zhang; Pan Wu; Shihong Zhang; Jiarui Zhu; Chuan Luo; Qiang Li (Journal of Environmental Chemical Engineering, 2026)

Preparation and evaluation of silicate stabilized FeS nanoslurry for in-situ remediation of hexavalent chromium - Ning-Ning Xing; Hong-Ling Zhang; Pan-Pan Mu; Hui Jiang; Hong-Bin Xu (Chemical Engineering Journal, 2026)

Engineering an “nano-antibiotic”: Synergistic catalytic bacterial killing via metal-phenolic network accelerating Fe(III)/Fe(II) cycle on MIL-101(Fe) - Qin Zhang; Xiaoming Song; Yifan Zhou; Lulu Pan; Xuemin Mu; Xiaolin Wang; Yanyan Li; Xiuhua Zhao (Chemical Engineering Journal, 2026)

Tannic acid protects against lapatinib-induced hepatotoxicity by inhibiting cathepsin activity and repairing lysosomal membrane permeabilization - Yuan Mu; Zengyue Pan; He Zhao; Xiangliang Huang; Nini Zhang; Zhifei Xu; Bo Yang; Qiaojun He; Xiaochun Yang; Peihua Luo; Hao Yan (Toxicology and Applied Pharmacology, 2026)

Bioelectrochemical carbon monoxide methanation in mixed-culture microbial electrolysis cells: Performance, electron transfer pathways and microbial succession - Guannan Zhou; Dandan Chen; Houyun Yang; Yixuan Wang; Fazhi Xie; Zhicheng Pan; Yang Mu (Environmental Research, 2026)

Transformation of selenium fractions driven by freeze-thaw cycles in two soils: Soil aggregate reconstruction and microbial community response - Mengqin Ren; Jiacheng Wu; Yumeng Liu; Lei Pan; Haotian Gong; Yuxin Mu; Min Wang; Hui Zhai (Environmental Research, 2026)

Nonlinear microbial thresholds drive non-additive soil greenhouse gas responses to compound climate extremes - Zehao Lv; Gangsheng Wang; Daifeng Xiang; Shuhao Zhou; Wanyu Li; Shanshan Qi; Yajing Han; Zirui Mu; Yilei Zhong; Shuang Li; Yuhao Pan; Jiahe Liu (Agricultural and Forest Meteorology, 2026)

Alantolactone inhibits T-cell lymphoma progression by suppressing CD47 expression via the PI3K/AKT and ERK signaling pathways - Xiaodong Li; Ningbo Pang; Yingcong Chen; Tingting Pan; Wenwen Sun; Bingrong Chen; Fuyi Xie; Yinyu Mu; Ni Li (Apoptosis, 2026)

Deciphering the mechanisms underlying regional heterogeneity of high-temperature Daqu through integrated electronic sensory, volatilome, and microbiome analysis - Yu Mu; Hong Zhang; Yingdong Pan; Ziyou Tian; Ying Huang; Liang Yang; Chunlin Zhang; Chi Zhao; Dong Li; Xudong Liu; Li Jiang (International Journal of Food Microbiology, 2026)

A physics-guided and scene-adaptive water index for consistent surface water mapping across regions and seasons - Shanchuan Guo; Pengfei Tang; Zilong Xia; Haowei Mu; Xiaoquan Pan; Peng Zhang; Yu Chen; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Sustainable Mn-Ni-Co recovery from complex secondary resources through process-chain engineering and life-cycle environmental assessment - Meichen Pan; Yusheng Tang; Ziyuan Liu; Zhe Tan; Yibo Yang; Panpan Mu; Xiaoguang Zhang (Chemical Engineering Journal, 2026)

Suicide attempt risk among patients receiving methylphenidate: a retrospective cohort study - Tai-Long Pan; Li-Chi Chen; Ju-Wei Hsu; Ya-Mei Bai; Shih-Jen Tsai; Tzeng-Ji Chen; Mu-Hong Chen (Psychopharmacology, 2026)
Background Methylphenidate may reduce suicide risk among patients with attention-deficit hyperactivity disorder. Several studies have noted that the association between methylphenidate use and suicidality is weakening. Methods Data were collected from Taiwan’s National Health Insurance Research Database to assess the association between methylphenidate exposure and suicide attempt risk across two exposure periods (main analysis: 2001–2002; duplication analysis: 2004–2005). We compared suicide attempt risk between patients who initiated methylphenidate treatment and those with no recorded psychiatric treatment or methylphenidate exposure during the same period. Results In both the main and duplication analyses, patients receiving methylphenidate exhibited a higher subsequent risk of suicide attempts than unexposed individuals. A duration–response pattern was observed in both cohorts: the hazard ratio of suicide attempts declined with longer cumulative methylphenidate use, from 1.60/1.84 for < 30 days to 1.45/1.65 for ≥ 180 days. Because hazard ratios were closely aligned across 2001–2002 and 2004–2005, the association of methylphenidate with reduced suicide attempt risk did not appear to decrease over time. Discussion Longer use of methylphenidate was associated with a lower risk of subsequent suicide attempts among patients in Taiwan receiving methylphenidate. The beneficial effect of methylphenidate on suicide risk remained consistent over time.

Optimisation and bioactivity evaluation of Brassica rapa L. seed oil extraction using novel green dimethyl ether extraction - Wan Xiao-Fu; Yimuranjiang Subuhati; He Tian; Miao-Miao Wang; Jia-Xin Yang; Le Pan; Mu-Chun Li (Natural Product Research, 2026)

Acid-base imbalance electrolytic cell (AB-EC) for efficient treatment of acid mine drainage (AMD): Metal recovery and hydrogen production - Haoyang Song; Zhudi Chen; Jinyuan Jiang; Wei Tan; Zhaocong Ren; Mu Feng; Dongni Shi; Hongke Qin; Lei He; Xiaojun Pan; Kuk Cho (Journal of Environmental Chemical Engineering, 2026)

Cover Image - Yinnan Mu; Weini Zhang; Pan Qin; Wenxing Li; Zhengwei Cui; Yang Ding; Jingqun Ao; Jiangtao Gao; Xinhua Chen (Reviews in Aquaculture, 2026)
The cover image is based on the article Elucidating the Immunological Basis of Large Yellow Croaker Larimichthys crocea Offers New Strategies for Its Disease Management by Yinnan Mu et al., https://doi.org/10.1111/raq.70164 . image

Elucidating the Immunological Basis of Large Yellow Croaker Larimichthys crocea Offers New Strategies for Its Disease Management - Yinnan Mu; Weini Zhang; Pan Qin; Wenxing Li; Zhengwei Cui; Yang Ding; Jingqun Ao; Jiangtao Gao; Xinhua Chen (Reviews in Aquaculture, 2026)
Large yellow croaker Larimichthys crocea is a major mariculture species in China, achieving an annual yield of 292,615 tons by 2024. Commercial production faces considerable challenges from disease outbreaks, necessitating comprehensive immune mechanism research. Through comprehensive genomic and transcriptomic investigations, scientists have identified distinguishing characteristics within the L. crocea immune system, encompassing robust innate defense mechanisms, marked by the expansion of pattern recognition receptor lineages, antimicrobial peptide gene families, and antiviral defense‐related genes, and well‐developed adaptive immune capabilities. The current review outlines the molecular foundations underlying immune responses in L. crocea , highlighting the cooperative interplay between innate and adaptive defense systems when confronting pathogenic threats and environmental fluctuations. It bridges basic scientific inquiry with practical aquaculture implementation, exploring disease control strategies. Available evidence indicates possibilities for strengthening disease resistance through precision immunomodulation and improved aquaculture methods. Priority research areas encompass elucidating host‐pathogen relationships and establishing practical disease prevention protocols for industrial‐scale operations.

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Understanding the tradeoff between the flood risk and the hydropower benefit from the integrated flood control operation of a reservoir group and a flood detention basin - Zhenyu Mu; Dedi Liu; Zhenyu Wang; Yuling Zhang; Pan Liu; Lihua Xiong; Jie Chen; Hua Chen; Jiabo Yin (Journal of Hydrology, 2026)

A combined biochar and biomineralization approach for enhanced soil Pb immobilization under accelerated aging - Huicong Hu; Zhengtao Shen; Chao-Sheng Tang; Wen Mu; Mengtao Wang; Sensen Li; Xiaohua Pan; Huan Liu; Bao-Jun Wang (Journal of Environmental Sciences, 2026)

Analysis of EVA gloves vibration reduction mechanism in a zero-gravity, low-pressure environment - Yanpu Mu; Hao Fu; Yizhen Zheng; Yuefeng Li; Xudong Pan (Advances in Space Research, 2026)

Application of Fenton Iron Sludge Coupled with Anaerobic Digestion for Pharmaceutical Wastewater Treatment: Performance and Mechanism - Zhongyi Zhang; Xinming Yang; Linsen Mu; Shuang Zhang; Yushan Zheng; Fang Zhang; Yang Pan; Zhuangyuan Hao (Water, Air, & Soil Pollution, 2026)

Ultrasound-enhanced ferulic acid treatment modulates starch gel structure to inhibit retrogradation in rice starch during storage - Chen Tian; Yuxin Mu; Qianyu Hang; Xingbo Zhuang; Leiqing Pan; Cheng Zhang; Chao Ding; Qiang Liu (Journal of Stored Products Research, 2026)

A flexible methanol production process scheduled by carbon price fluctuation: Techno-economic and risk analysis - Jincheng Pan; Jiusheng Mu; Jing Ding; Chundong Zhang; Hui Wan; Guofeng Guan (Journal of Cleaner Production, 2026)

Assessing the variations of the available flood storage capacity in a flood retention basin due to the changing environment - Yuling Zhang; Dedi Liu; Zhenyu Wang; Zhenyu Mu; Jiaoyang Wang; Pan Liu; Lihua Xiong; Jie Chen; Hua Chen (Journal of Environmental Management, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

A weakly supervised approach for large-scale agricultural parcel extraction from VHR imagery via foundation models and adaptive noise correction - Wenpeng Zhao; Shanchuan Guo; Xueliang Zhang; Pengfei Tang; Xiaoquan Pan; Haowei Mu; Chenghan Yang; Zilong Xia; Zheng Wang; Jun Du; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

COL8A1-positive cancer-associated fibroblasts are drivers of 5-fluorouracil resistance in colorectal cancer - Muzi Ding; Yue Li; Zixuan Liu; Shangshang Hu; Jinwei Lou; Yuhan Chen; Jian Qin; Mu Xu; Huiling Sun; Tao Xu; Shukui Wang; Yuqin Pan (Apoptosis, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dual-readout digital colorimetric assay for zearalenone in corn based on alkaline phosphatase mediated growth of Prussian blue nanoparticles - Shanghong Ji; Tingtiao Pan; Weizhen Xu; Song Tang; Guodong Mu; Zeyu Hu; Yu Zhou (Food Chemistry, 2026)

Improving hydro-mechanical response of heavy metal contaminated soil to rainfall events through combination of biochar and microbial induced carbonate precipitation (BM) treatment - Huicong Hu; Chao-Sheng Tang; Zhengtao Shen; Xiaohua Pan; Kai Gu; Mengtao Wang; Wen Mu; Bao-Jun Wang; Huan Liu; Zhihan Ji; Weiqiang Li (Engineering Geology, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Revealing the dynamic biological flow between eastern and western China from the perspective of ecological network - Haowei Mu; Shanchuan Guo; Kaixuan Pan; Bo Yuan; Zhou Fang; Xingang Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2026)

Enzyme activity-enhanced MIL101(Fe) loaded PdSn Nanoenzymes enable ultrasensitive detection of oxytetracycline in foods - Yuanpei Pan; Zhaode Mu; Min Qing; Yijie Wu; Meili Deng; Lijuan Bai (Food Chemistry, 2025)

ERO1A-positive tumor epithelial cells in colorectal cancer progression: a multi-omics perspective - Shangshang Hu; Jinwei Lou; Yuhan Chen; Muzi Ding; Jian Qin; Junjie Nie; Yue Li; Zixuan Liu; Mu Xu; Huiling Sun; Qianni Xiao; Yuqin Pan; et al. (Apoptosis, 2025)

Anti-melanogenic effect and mechanism of oxypaeoniflorin derived from edible Paeonia ostii flower on melanogenesis in B16F10 cells and zebrafish - Kejie Peng; Yixuan Wang; Zhangtie Wang; Jing Wang; Yuhang Zhu; Qiannan Pan; Yumeng Li; Jian Mu; Xiuxin Zhang; Baiyi Lu (Food Bioscience, 2025)

Effect of mixing and compaction methods on the physical properties, strength and microstructure of phase change material-modified soils under freeze-thaw process - Jun Bi; Yuxuan Pan; Wenxuan Mu; Mingyi Zhang; Guiyu Zhao; Haoxin Chen; Pengfei Liu (Cold Regions Science and Technology, 2025)

Plant survival strategies under heterogeneous salt stress: remodeling of root architecture, ion dynamic balance, and coordination of metabolic homeostasis - Minghui Zhang; Menghan Pan; Hongjiao Li; Bingxiang Liu; Shenqi Qiao; ChangMing Ma; Hongxiang Mu; Wenhao Zhao; Jinyu Guo (Plant and Soil, 2025)

Research progress on the separation, purification, and utilization of beryllium from beryllium-containing minerals - Mengchen Xiao; Yibo Yang; Yusheng Tang; Panpan Mu; Hao Liu; Xiaoguang Zhang; Dean Pan (Process Safety and Environmental Protection, 2025)

Optimizing biogas residue composting: Impact of biochar and zeolite co-loaded with lignocellulose-degrading microbial agents on degradation, humification, and microbial ecology - Hong Chang; Ruian Lin; Xiaohong Su; Xinrui Xu; Wei Liu; Yilin Zhang; Zeyan Mu; Xin Wang; Anina James; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

A MOF-on-MOF heterostructure-based electrochemical aptasensor for ultrasensitive detection of tobramycin in food - Meili Deng; Zhaode Mu; Yijie Wu; Yuanpei Pan; Lijuan Bai (Journal of Environmental Chemical Engineering, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Hydroquinone Hydroxypropyl-β-cyclodextrin Inclusion Complex Based Topical Cream as an Effective Treatment of Melasma by Releasing Hydroquinone in a Controlled Manner - Yinling Mu; Hongbing Liu; Xianglin Guo; Yiyu Liu; Wanbing Pan; Fan Zhao; Haibing He; Jingxin Gou; Xing Tang; Tian Yin; Yu Zhang (Pharmaceutical Research, 2025)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Mining robust in situ phosphorus-accumulating organisms via single-cell RACS-Culture for rational ecosystem engineering - Xiaoyan Jing; Yanhai Gong; Yishang Ren; Liyan Wang; Runzhi Mu; Pengcheng Sun; Zhidian Diao; Yu Meng; Liming Huang; Xixian Wang; Jia Zhang; Jiaxuan Luan; et al. (Water Research, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

The association between maternal exposure to ten neonicotinoid insecticides and preterm birth in Guangxi, China - Dongxiang Pan; Lihong Zhou; Changhui Mu; Mengrui Lin; Xiaogang Wang; Qian Liao; Lidi Lei; Shun Liu; Dongping Huang; Xiaoqiang Qiu; Xiaoyun Zeng (Environmental Pollution, 2025)

County-level coordination between urbanization and ecological change in dryland urban agglomerations: A quantitative approach based on remote sensing - Chunqiang Li; Shanchuan Guo; Zilong Xia; Xiaoquan Pan; Haowei Mu; Hong Fang; Pengfei Tang; Peijun Du (Journal of Geographical Sciences, 2025)

Poly(aryl piperidine) anion exchange membrane with self-assembled siloxane crosslinked networks for efficient ion separation in alkaline waste treatment via electrodialysis - Yazhen Jiang; Tong Mu; Ning Ding; Yangke Pan; Geting Xu; Junbin Liao; Edison Huixiang Ang; Jiangnan Shen (Desalination, 2025)

Evolution characteristics of multi-physical fields distributions during the whole life cycle of PEMFC - Panxing Jiang; Fan Wu; WanQiu Yu; Zhiping Huang; XinHao Huang; Zhigang Zhan; Shang Li; Mu Pan (Chemical Engineering Journal, 2025)

Green and sustainable strategy for separation and recovery of high-value fluorine and magnesium from fluorine slag by alkaline roasting-hydrometallurgy - Hang Zhao; Xiaoguang Zhang; Guosai Jiang; Feihua Yang; Yanling Wu; Panpan Mu; Haile Yan; De’an Pan (Journal of Environmental Chemical Engineering, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Research on extraction of valuable metals from solid waste by deep eutectic solvents - A review - Chenye Yang; Jianying Zhao; Panpan Mu; Guosai Jiang; Zhe Tan; Xiaoguang Zhang; Dean Pan (Process Safety and Environmental Protection, 2025)

Effects of neonicotinoid pesticide exposure in the first trimester on gestational diabetes mellitus based on interpretable machine learning - Dongxiang Pan; Lihong Zhou; Changhui Mu; Mengrui Lin; Yonghong Sheng; Yang Xu; Dongping Huang; Shun Liu; Xiaoyun Zeng; Virasakdi Chongsuvivatwong; Xiaoqiang Qiu (Environmental Research, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Sustainable and energy-efficient degradation of acetaminophen in water using an optimized Fenton-like system with iron-doped graphitic carbon nitride catalyst - Xiaoping Mu; Dongli Wang; Dongqin He; Jianqiang Sun; Xiangliang Pan; Yifeng Zeng; Hongwei Luo (Journal of Environmental Chemical Engineering, 2025)

Distinguishing the botanical origins of rare honey through untargeted metabolomics and machine learning interpreting flavonoid profiles - Sha Yan; Yuzhe Yuan; Fei Pan; Guodong Mu; Haitao Xu; Xiaofeng Xue (Food Chemistry, 2025)

Bomb-produced radiocarbon dynamics and salinity-water isotopes relationship at two stations in the tropical South Pacific Ocean and implications for upper ocean processes - Yongqi Liang; Liping Zhou; Yongrui An; Pan Gao; Xuefa Shi; Mu Huang; Kexin Liu (Journal of Oceanography, 2025)

Development of a colloidal gold immunochromatographic strip for the rapid on-site detection of Ecytonucleospora hepatopenaei (EHP) - Xianzhi Meng; Yixiang Yu; Dandan Ma; Mingxin Mu; Quan Sun; Quanlin Liu; Xiaodong Fan; Tian Li; Jie Chen; Guoqing Pan; Zeyang Zhou (Journal of Invertebrate Pathology, 2025)

Mitochondrial mechanism of florfenicol-induced nonalcoholic fatty liver disease in zebrafish using multi-omics technology - Lin Zhang; Yang Du; Yameng Li; Tiancai Wang; Yecan Pan; Xiaofeng Xue; Xiyan Mu; Jing Qiu; Yongzhong Qian (Journal of Hazardous Materials, 2025)

Microbial mechanisms of mixed planting in regulating soil phosphorus availability across different stand ages in Chinese fir plantations - Chang Pan; Weijie Mu; Wenruinan Yu; Chenchen Sun; Jiahuan Guo; Liangxi Chen; Yuanchun Yu; Xiaogang Li (Journal of Environmental Management, 2025)

Dimensionality reduction of high-solid anaerobic digestion flow pattern: Flow velocity distribution model and control strategy - Zhenni Pan; Yuying Hu; Tengfang Hu; Haoran Mu; Huai Z. Li (Bioresource Technology, 2025)

Comparing on-line continuous movement decoding with joints unconstrained and constrained based on a generic musculoskeletal model - Lizhi Pan; Zhongyi Ding; Haifeng Zhao; Ruinan Mu; Jianmin Li (Medical & Biological Engineering & Computing, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Effect of microplastics concentration and size on pollutants removal and antibiotic resistance genes (ARGs) generation in constructed wetlands: A metagenomics insight - Lin Liang; Weiliang Pan; Merui Mu; Lin Zhang; Xiangyu Yang; Ruina Zhang; Lianfeng Du; Xuan Guo (Journal of Hazardous Materials, 2025)

Digital one-pot SHERLOCK assisted superfast and reverse transcription free method for circulating microRNA absolute quantification - Zheyu Zou; Juxin Yin; Liping Xia; Weihong Yin; Ke Liu; Yating Pan; Kai Hu; Yehong Gui; Jianjian Zhuang; Duo Xiao; Ying Mu (Chemical Engineering Journal, 2025)

Mutation of MeMinD increased amyloplast size with a changed starch granule morphologenesis and structures in cassava storage roots - Xiaohua Lu; Yajie Wang; Mu Pan; Songbi Chen; Ruimei Li; Mengting Geng; Yinhua Chen; Jiao Liu; Jianchun Guo; Yuan Yao (Carbohydrate Polymers, 2025)

Acetylcholinesterase inhibitory phloroglucinols from tropic Rhodomyrtus tomentosa - Ling-Yun Chen; E-E Luo; Yu Pan; Cheng-Qin Liang; Mu-Yuan Yu; Xu-Jie Qin (Phytochemistry, 2024)

Quantifying the drought sensitivity of vegetation types in northern China from 1982 to 2022 - Bo Yuan; Shanchuan Guo; Xingang Zhang; Haowei Mu; Shengpeng Cao; Zilong Xia; Xiaoquan Pan; Peijun Du (Agricultural and Forest Meteorology, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Study on the shielding of harmful components in spent FCC catalyst tailings - Haojie Zhang; Jianying Zhao; Panpan Mu; Xiaoguang Zhang; Shaogang Zhang; De’an Pan (Process Safety and Environmental Protection, 2024)

Balancing photovoltaic development and cropland protection: Assessing agrivoltaic potential in China - Zilong Xia; Yingjie Li; Shanchuan Guo; Nan Jia; Xiaoquan Pan; Haowei Mu; Ruishan Chen; Meiyu Guo; Peijun Du (Sustainable Production and Consumption, 2024)

Risk assessment of high maturity lacustrine shale oil reservoir based on pore-fracture connectivity and decane accessibility, Ordos Basin (China) - Jianjiang Wen; Mengdi Sun; Bingsong Yu; Mehdi Ostadhassan; Tomasz P. Blach; Yeping Ji; Phung Vu; Liliana de Campo; Chunming Wu; Jingfu Mu; Zijie Ren; Xin Tian; et al. (Marine and Petroleum Geology, 2024)

The role and mechanism of β-catenin-mediated skeletal muscle satellite cells in osteoporotic fractures by Jian-Pi-Bu-Shen formula - Yanghua Tang; Zhuosong Mu; Dong Pan; Renqi Liu; Shenghu Hong; Zhenfei Xiong (Journal of Molecular Histology, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Effect of composite cultivation on the meat quality of crucian carp (Carassius auratus) - Yin Zhang; Yunlong Mu; Linguo Wang; Qing Zeng; Pengcheng Zhang; Haichuan Peng; Qiuyue Chen; Jianlin Jia; Zhongli Pan; Qing Li (Aquaculture International, 2024)

Efficient conversion process and mechanism of bromine in bromine-rich saline wastewater - Jixian Wu; Panpan Mu; Xiaoguang Zhang; Guosai Jiang; Zhe Tan; De'an Pan (Journal of Cleaner Production, 2024)

Suppressing leakage current and charge accumulation via perovskite interface morphology regulation for efficient light-emitting diodes - Yongjian Chen; Xiankan Zeng; Cheng Yan; Shiyu Yang; Lunyao Pan; Chenglong Li; Maolin Mu; Wen Li; Guanqi Tang; Weiqing Yang (Chemical Engineering Journal, 2024)

Spatiotemporal joint analysis of PM2.5 and Ozone in California with INLA approach - Jianan Pan; Kunyang He; Kai Wang; Qing Mu; Chengxiu Ling (Journal of Environmental Management, 2024)

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Multi-omics insights into biogeochemical responses to organic matter addition in an acidic pit lake: Implications for bioremediation - Zhixiang She; Jin Wang; Xin Pan; Ding Ma; Yijun Gao; Shaoping Wang; Xin Chuai; Yang Mu; Zhengbo Yue (Water Research, 2024)

The positive effect of the enzyme inducer (MnSO4) on the formation of humic substance in rice straw composting by stimulating key microorganisms - Linying Mu; Runshi Dong; Jiaqi Wang; Jieyu Yue; Lina Pan; Caihong Song; Zimin Wei (Science of The Total Environment, 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Performance of microbial inoculation and tricalcium phosphate on nitrogen retention and conversion: Core microorganisms and enzyme activity during kitchen waste composting - Taha Ahmed Mohamed; Zimin Wei; Mohamed Mohaseb; Wu Junqiu; Taha El Maghraby; Xiaomeng Chen; Yousif Abdelrahman Yousif Abdellah; Daichen Mu; Mohamed El Kholy; Chaonan Pan; Ayodeji Bello; Guangren Zheng; et al. (Journal of Environmental Management, 2024)

High organic aerosol in the low layer over a rural site in the North China Plain (NCP): Observations based on large tethered balloon - Jiannong Quan; Juntao Huo; Chenglong Zhang; Yubing Pan; Pengkun Ma; Zhiheng Liao; Zhigang Cheng; Xingcan Jia; Qianqian Wang; Qingyan Fu; Yujing Mu; Fei Hu (Science of The Total Environment, 2024)

Enhancing envrionmental sustainability via interval optimization for low-carbon economic dispatch in renewable energy power systems: Leveraging the flexible cooperation of wind energy and carbon capture power plants - Jianzhao Song; Zhong Zhang; Yunye Mu; Xingyu Wang; Haipeng Chen; Qingze Pan; Yang Li (Journal of Cleaner Production, 2024)

A novel Vibrio alginolyticus phage and its therapy application in Portunus trituberculatus larvae - Ruqian Cai; Dengfeng Li; Weinan Qin; Wei Lin; Lingting Pan; Minhua Qian; Fei Wang; Chunlin Wang; Changkao Mu; Yigang Tong (Aquaculture, 2024)

Effects of bubble and reactor shape on cold plasma yeast inactivation - Ying Wang; Guanting Pan; Yining Li; Longtao Mu; Mingwei Zhao; Yu Zheng (Journal of Food Engineering, 2024)

Preparation of chromium oxide by hydrothermal reduction of sodium chromate aqueous solution with hydrogen and application to chromite ore processing - Panpan Mu; Hongling Zhang; De'an Pan; Shuting Liang; Taiping Lou; Hongbin Xu (Hydrometallurgy, 2024)

Somatic embryo induction and plantlet regeneration of Canna × generalis from immature zygotic embryo - Zu-yan Gan; Mu-lin Shu; Feng Yang; Guo-fang Wang; Wen-e Zhang; Xue-jun Pan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Characterization of the differences in aroma-active compounds in strong-flavor Baijiu induced by bioaugmented Daqu using metabolomics and sensomics approaches - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Hanlan Tang; Qianglin Pan; Huifang Tang (Food Chemistry, 2023)

Self-healing polyurethane coatings based on dynamic chemical bond synergy under conditions of photothermal response - Kang Chen; Haoxin Zhu; Zhiyi Zhang; Yingqing Shao; Qianhui Yu; Xinlei Cao; Siyan Pan; Xin Mu; Zhenhua Gao; Di Wang; Shuangying Wei; Shuaiyuan Han (Chemical Engineering Journal, 2023)

Biological neutralization of bauxite residue with fermented waste sludge and bio-acid, and the microbial ecological restoration - Dainan Qin; Xiaotong Tan; Xin Zhao; Lulu Qian; Yuanyuan Nie; Xiaolin Pan; Qun Gao; Mu Peng; Yang Liu; Xiaoyu Han (Chemical Engineering Journal, 2023)

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

Engineering Escherichia coli for high-level production of lacto-N-fucopentaose I by stepwise de novo pathway construction - Zeyu Li; Yingying Zhu; Zhaolin Huang; Pan Zhang; Wenli Zhang; Wanmeng Mu (Carbohydrate Polymers, 2023)

New insights into enhanced biodegradation of 4-bromphenol in a nitrate-reducing system: Process performance and mechanism - Jing Wang; Qiang Chi; Ling Pan; Ranran Zhang; Yang Mu; Jinyou Shen (Water Research, 2023)

Green recovery of Li, Ni, and Mn from spent xLi2MnO3·(1-x)LiMO2 cathode materials: Experimental study and mechanism analysis - Yifan Wang; Qijun Zhang; Xiaoxia Bai; Panpan Mu; Xiaoguang Zhang; Wei Wang; Zhe Tan; Zhenhuan Zhao; De'an Pan (Chemical Engineering Journal, 2023)

Identification of sweet spots in shale-type and siltstone-type “shale oil systems”: A case study of the Chang 7 Member in Ordos Basin - Songqi Pan; Qiulei Guo; Caineng Zou; Zhenhua Jing; Ming Yuan; Ying He; He Zheng; Ying Mu; Zhi Yang; Shixiang Li; Xinping Zhou; Songtao Wu; et al. (Science China Earth Sciences, 2023)

Enhancing lead immobilization by biochar: Creation of “surface barrier” via bio-treatment - Huicong Hu; Chao-Sheng Tang; Zhengtao Shen; Xiaohua Pan; Kai Gu; Xiaoliang Fan; Chao Lv; Wen Mu; Bin Shi (Chemosphere, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Dysfunction of NRG1/ErbB4 Signaling in the Hippocampus Might Mediate Long-term Memory Decline After Systemic Inflammation - Yu-zhu Gao; Xin-miao Wu; Zhi-qiang Zhou; Pan-miao Liu; Jian-jun Yang; Mu-huo Ji (Molecular Neurobiology, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Impact of Climate Change on Water Transfer Scale of Inter-basin Water Diversion Project - Tao Bai; Lei Li; Peng-fei Mu; Bao-zhu Pan; Jin Liu (Water Resources Management, 2023)

Experimental study on in-plane behavior of composite frame slabs and the influence of out-of-plane effect - Wen-Hao Pan; Mu-Xuan Tao; Chuan-Hao Zhao; Ran Ding; Li-Yan Xu (Engineering Structures, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Developmental and reproduction toxicity studies of Biolimus A9 in SD rats - Shidong Qiu; Yang Liu; Yuanhang Pan; Yuji Liang; Liyuan Zhou; Xiaobo Wang; Peilu Sun; Suling Teng; Dan Wang; Yanling Mu (Reproductive Toxicology, 2023)

Comprehensive analysis for the bioturbation effect of space mutation and biofortification on strong-flavor Daqu by high-throughput sequencing, volatile analysis and metabolomics - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Yi Dong; Chao Wang; Xiaojun Wang; Qianglin Pan; Huifang Tang (Food Chemistry, 2023)

Geographical distance, host evolutionary history and diet drive gut microbiome diversity of fish across the Yellow River - Baozhu Pan; Xu Han; Ke Yu; He Sun; Rong Mu; Chun‐Ang Lian (Molecular Ecology, 2023)
Fish represent a large part of the taxonomic diversity of vertebrates and are of high commercial value. However, the factors influencing the gut microbiota composition of freshwater fish over large spatial scales remain unclear. Therefore, this study explored gut microbiome diversity in 24 fish species from the Yellow River, which spans over 1500 km across China. The results showed that geographical distance, host phylogeny and diet significantly influenced gut microbial community diversity, whereas sex, body length and body weight had minimal influence. Geographical distance was the primary factor shaping gut microbiota, and dissimilarity in microbial community structure increased with an increase in geographical distance, which was mainly driven by dispersal limitation. The microbial communities were more homogeneous at higher host taxonomic resolutions due to the dominant role of homogeneous selection in community convergence. Phylosymbiosis was observed across all host species, with a stronger pattern in Cypriniformes, which harbour host‐specific microbial taxa. Host diet explained little variation in gut microbiome diversity, although it was significant for all diversity metrics tested. These findings collectively suggest that the geographical and host‐based patterns of fish gut microbiota tend to be shaped by different ecological forces across the Yellow River. The present work provides a robust assessment of multiple factors driving fish gut microbial community assembly and offers insight into the mechanisms underlying shifts in fish gut microbiota in rivers across large spatial scales.

Two-year online measurements of volatile organic compounds (VOCs) at four sites in a Chinese city: Significant impact of petrochemical industry - Jiangshan Mu; Yingnan Zhang; Zhiyong Xia; Guolan Fan; Min Zhao; Xiaoyan Sun; Yuhong Liu; Tianshu Chen; Hengqing Shen; Zhanchao Zhang; Huaicheng Zhang; Guang Pan; et al. (Science of The Total Environment, 2023)

Effect of 4 °C and ice temperature on umami-enhancing nucleotides of conditioned pork - Yin Zhang; Yingjie Zhang; Hui Li; Ting Bai; Qin Qian; Haichuan Peng; Yunlong Mu; Linguo Wang; Baohua Liu; Jie Chen; Zhongli Pan; Dayu Liu; et al. (Food Chemistry, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Evaluating the survival of Aspergillus niger in a highly polluted red soil with addition of Phosphogypsum and bioorganic fertilizer - Lingzi Meng; Shang Pan; Limin Zhou; Choochad Santasup; Mu Su; Da Tian; Zhen Li (Environmental Science and Pollution Research, 2022)

Lithology identification method based on integrated K-means clustering and meta-object representation - Zhimin Cao; Can Yang; Jian Han; Haiwei Mu; Chuan Wan; Pan Gao (Arabian Journal of Geosciences, 2022)

Preparation and Evaluation of Novel Supersaturated Solid Dispersion of Magnolol - Jing Zhao; Pan Gao; Chengqiao Mu; Jingqi Ning; Wenbin Deng; Dongxu Ji; Haowei Sun; Xiangrong Zhang; Xinggang Yang (AAPS PharmSciTech, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Plant invasion alters latitudinal pattern of plant‐defense syndromes - Mu Liu; Yuanfei Pan; Xiaoyun Pan; Alejandro Sosa; Dana M. Blumenthal; Mark Van Kleunen; Bo Li (Ecology, 2021)
The relationship between herbivory and latitude may differ between native and introduced populations of invasive plants, which can generate latitudinal heterogeneity in the strength of enemy release. However, still little is known about how latitudinal heterogeneity in herbivore pressure influences latitudinal variation in defense phenotypes of invasive plants. We tested how latitudinal patterns in multi‐variate defense syndromes differed between native (Argentinian) and introduced (Chinese) populations of the invasive herb Alternanthera philoxeroides . In addition, to better understand the drivers underlying latitudinal patterns, we also tested whether associations of defense syndromes with climate and herbivory differed between native and introduced ranges. We found that native plant populations clustered into three main defense syndromes associated with latitude. In contrast, we only found two defense syndromes in the introduced range. One matched the high‐latitude syndrome from the native range, but was distributed at both the northern and southern range limits in the introduced range. The other was unique to the introduced range and occurred at mid‐latitudes. Climatic conditions were associated with variation in syndromes in the native range, and climatic conditions and herbivory were associated with variation in syndromes in the introduced range. Together, our results demonstrate that plants may under the new environmental conditions in the introduced range show latitudinal patterns of defense syndromes that are different from those in their native range. This emphasizes that geographical dependence of population differentiation should be explicitly considered in studies on the evolution of defense in invasive plants.

Correction to: Preparation and Evaluation of Self-emulsifying Drug Delivery System (SEDDS) of Cepharanthine - Pan Gao; Zhujun Jiang; Qiao Luo; Chengqiao Mu; Mengsuo Cui; Xinggang Yang (AAPS PharmSciTech, 2021)

Preparation and Evaluation of Self-emulsifying Drug Delivery System (SEDDS) of Cepharanthine - Pan Gao; Zhujun Jiang; Qiao Luo; Chengqiao Mu; Mengsuo Cui; Xinggang Yang (AAPS PharmSciTech, 2021)

Characterization of expansin genes and their transcriptional regulation by histone modifications in strawberry - Qin Mu; Xianyang Li; Jianhua Luo; Qinwei Pan; Yi Li; Tingting Gu (Planta, 2021)

Clinical characteristics of re-hospitalized COVID-19 patients with recurrent positive SARS-CoV-2 RNA: a retrospective study - Lei Pan; Runsheng Wang; Na Yu; Chao Hu; Junhong Yan; Xiaomin Zhang; Tao Wang; Jungui Hao; Fuquan Gao; Tonggang Liu; Jing Wang; Xiaojing Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

FucP mediates fucose to regulate T3SS in Edwardsiella piscicida and promotes intestinal colonization in Tilapia - Tingqi Ye; Jiayan Wu; Cuimin Mu; Guangchen Pan; Jiakang Chen; Xuepeng Wang (Aquaculture International, 2021)

The role of UhpA in regulating the virulence gene expression in Edwardsiella piscicida - Tingqi Ye; Cuimin Mu; Jiakang Chen; Guangchen Pan; Xuepeng Wang (Journal of Fish Diseases, 2021)
Edwardsiella piscicida ( E. piscicida ) is an important fish pathogen. However, the mechanism of Glu6P transport regulatory protein UhpA how to affect the virulence gene expression in E. piscicida is still unclear. The results in this study showed that the metabolism‐related gene expression of cysteine synthase (orf 1134) and sulphate transporter ( ych M) in the uhp A mutant strain Δ uhpA was 0.76‐fold and 0.68‐fold lower than the ones in the wild strains ( p uhp A strain was 0.80‐fold and 0.72‐fold lower than the ones in the wild strains ( p fliC and flgN in the Δ uhpA was 1.51‐fold and 1.21‐fold higher than the ones in the wild strains ( p esrB and esrC ) and T6SS ( evpB and evpC ) in the Δ uhpA was 1.27‐fold, 1.13‐fold, 1.28‐fold and 1.23‐fold higher than the ones in the wild strains ( p uhp A gene could regulate the key virulence gene expression, and the uhp A gene was associated with the pathogenicity of E. piscicida in fish.

The gut bacterial flora associated with brown planthopper is affected by host rice varieties - Zheng-Liang Wang; Hai-bo Pan; Wei Wu; Mu-Yu Li; Xiao-Ping Yu (Archives of Microbiology, 2021)

Overexpression of LncRNA PSMG3-AS1 Distinguishes Glioblastomas from Sarcoidosis - Liusheng Chen; Guanliang Wang; Zihui Xu; Kailong Lin; Sen Mu; Yicheng Pan; Mengya Shan (Journal of Molecular Neuroscience, 2020)

Safety of azithromycin in pediatrics: a systematic review and meta-analysis - Linan Zeng; Peipei Xu; Imti Choonara; Zhenyan Bo; Xiangchen Pan; Wenyan Li; Xiaofeng Ni; Tao Xiong; Can Chen; Leshan Huang; Shamim Ahmad Qazi; Dezhi Mu; et al. (European Journal of Clinical Pharmacology, 2020)
Purpose To evaluate the toxicity of azithromycin in neonates, infants, and children. Methods A systematic review was performed for relevant studies using Medline (Ovid), PubMed, Cochrane Central Register of Controlled Trials, EMBASE, CINAHL, and International Pharmaceutical Abstracts. We calculated the pooled incidence of adverse drug reactions (ADRs) associated with azithromycin based on prospective studies (RCTs and prospective cohort studies) and analyzed the risk difference (RD) of ADRs between azithromycin and placebo or other antibiotics using meta-analysis of RCTs. Results We included 133 studies with 4243 ADRs reported in 197,675 neonates, infants, and children who received azithromycin. The safety of azithromycin as MDA in pediatrics was poorly monitored. The main ADRs were diarrhea and vomiting. In prospective non-MDA studies, the most common toxicity was gastrointestinal ADRs (938/1967; 47.7%). The most serious toxicities were cardiac (prolonged QT or irregular heart beat) and idiopathic hypertrophic pyloric stenosis (IHPS). Compared with placebo, azithromycin did not show increased risk ADRs based on RCTs (risk difference − 0.17 to 0.07). The incidence of QT prolonged was higher in the medium-dosage group (10–30 mg/kg/day) than that of low-dosage group (≤ 10 mg/kg/day) (82.0% vs 1.2%). Conclusion The safety of azithromycin as MDA needs further evaluation. The most common ADRs are diarrhea and vomiting. The risk of the most serious uncommon ADRs (cardiac-prolonged QT and IHPS) is unknown.

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

Impacts of replacement of dietary fish oil by vegetable oils on growth performance, anti-oxidative capacity, and inflammatory response in large yellow croaker Larimichthys crocea - Hua Mu; Chaoqing Wei; Yanjiao Zhang; Huihui Zhou; Ying Pan; Jia Chen; Wenbing Zhang; Kangsen Mai (Fish Physiology and Biochemistry, 2020)

Testing the shifting defense hypothesis for constitutive and induced resistance and tolerance - Mu Liu; Xiaoyun Pan; Zhijie Zhang; Mark van Kleunen; Bo Li (Journal of Pest Science, 2020)

Regulation of flowering time via miR172-mediated APETALA2-like expression in ornamental gloxinia (Sinningia speciosa) - Xiao-yan Li; Fu Guo; Sheng-yun Ma; Mu-yuan Zhu; Wei-huai Pan; Hong-wu Bian (Journal of Zhejiang University-SCIENCE B, 2019)

Transcriptome analysis on chlorpyrifos detoxification in Uronema marinum (Ciliophora, Oligohymenophorea) - Chongnv Wang; William A. Bourland; Weijie Mu; Xuming Pan (Environmental Science and Pollution Research, 2018)

Toxicity of Chlorpyrifos and Dimethoate to the Ciliate Urostyla grandis, with Notes on Their Effects on Cell Ultrastructure - Weijie Mu; Alan Warren; Xuming Pan; Chen Ying (Journal of Ocean University of China, 2018)

Contrasting effects of specialist and generalist herbivores on resistance evolution in invasive plants - Zhijie Zhang; Xiaoyun Pan; Dana Blumenthal; Mark van Kleunen; Mu Liu; Bo Li (Ecology, 2018)
Invasive alien plants are likely to be released from specialist herbivores and at the same time encounter biotic resistance from resident generalist herbivores in their new ranges. The Shifting Defense hypothesis predicts that this will result in evolution of decreased defense against specialist herbivores and increased defense against generalist herbivores. To test this, we performed a comprehensive meta‐analysis of 61 common garden studies that provide data on resistance and/or tolerance for both introduced and native populations of 32 invasive plant species. We demonstrate that introduced populations, relative to native populations, decreased their resistance against specialists, and increased their resistance against generalists. These differences were significant when resistance was measured in terms of damage caused by the herbivore, but not in terms of performance of the herbivore. Furthermore, we found the first evidence that the magnitude of resistance differences between introduced and native populations depended significantly on herbivore origin (i.e., whether the test herbivore was collected from the native or non‐native range of the invasive plant). Finally, tolerance to generalists was found to be higher in introduced populations, while neither tolerance to specialists nor that to simulated herbivory differed between introduced and native plant populations. We conclude that enemy release from specialist herbivores and biotic resistance from generalist herbivores have contrasting effects on resistance evolution in invasive plants. Our results thus provide strong support for the Shifting Defense hypothesis.

Response of the freshwater diatom Halamphora veneta (Kützing) Levkov to copper and mercury and its potential for bioassessment of heavy metal toxicity in aquatic habitats - Weijie Mu; Kun Jia; Yan Liu; Xuming Pan; Yawen Fan (Environmental Science and Pollution Research, 2017)

Urinary levels of phthalate metabolites and associations with demographic characteristics in Korean adults - Kyoung-Mu Lee; Younglim Kho; Pan-gyi Kim; Seok-hwan Park; Jin-Heon Lee (Environmental Science and Pollution Research, 2017)

Fiber beam–column element model considering reinforcement anchorage slip in the footing - Wen-Hao Pan; Mu-Xuan Tao; Jian-Guo Nie (Bulletin of Earthquake Engineering, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Enhanced organic phosphorus detection in sediments by foam separation and 31P-NMR - Yuxin Shi; Tengfei Pan; Di Mu; Hongqin Wu; Qingqiang Meng; Shuting Qi (Environmental Chemistry Letters, 2014)

Transport of airborne Picea schrenkiana pollen on the northern slope of Tianshan Mountains (Xinjiang, China) and its implication for paleoenvironmental reconstruction - Yanfang Pan; Shun Yan; Hermann Behling; Guijin Mu (Aerobiologia, 2013)

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Small heat shock protein LimHSP16.45 protects pollen mother cells and tapetal cells against extreme temperatures during late zygotene to pachytene stages of meiotic prophase I in David Lily - Changjun Mu; Shaobo Wang; Shijia Zhang; Jiajia Pan; Ni Chen; Xiaofeng Li; Zhaoyan Wang; Heng Liu (Plant Cell Reports, 2011)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Toxic effects of antimony on photosystem II of Synechocystis sp. as probed by in vivo chlorophyll fluorescence - Daoyong Zhang; Xiangliang Pan; Guijin Mu; Jianlong Wang (Journal of Applied Phycology, 2010)

Soil erosion changes over the past five decades in the red soil region of Southern China - Yin Liang; Decheng Li; Xixi Lu; Xuan Yang; Xianzhang Pan; Huan Mu; Deming Shi; Bin Zhang (Journal of Mountain Science, 2010)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)